Analysis of Broiler Chicken Business Performance and Development Strategy at PT. Mitra Sinar Jaya Partner Farm, Nagekeo Branch, Using the LFA Approach: Analisis Keragaan dan Strategi Pengembangan Usaha Ayam Broiler pada Peternakan Mitra PT. Mitra Sinar Jaya Cabang Nagekeo dengan Pendekatan LFA - Ronaldus Don Piran; Maria Salestina Ngoni; Paulus Every Sudirman; Yohana Spayolin Sarina Paur (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
This study analyzed the performance of broiler chicken farming at a partner farm of PT. Mitra Sinar Jaya (MSJ) Nagekeo Branch and developed alternative business strategies using the Logical Framework Approach (LFA). A case study was conducted on one partner farm (Mrs. Apolonia To Sada) during the fourth production period of 2022 in Watu Gase Village, Boawae District, Nagekeo Regency. Business performance was measured through costs, revenues, income, and R/C ratio. LFA analysis included stakeholder analysis, problem analysis (problem tree), objective analysis (objective tree), and strategy analysis. Total revenue reached IDR 713,795,500.00, total costs were IDR 630,268,213.00, resulting in an income of IDR 83,527,287.00. The R/C ratio was 1.13, indicating that the business is profitable but remains vulnerable to feed price fluctuations. Recommended development strategies include: partner farmers expanding coops, optimizing capital, and increasing capacity; PT. MSJ Nagekeo Branch expanding markets, providing regular supervision, and prioritizing fair harvests for open and semi-closed coops; and the government offering guidance on financial management and proper broiler maintenance.